2010
DOI: 10.1182/blood-2009-07-235861
|View full text |Cite
|
Sign up to set email alerts
|

Redox regulation of T-cell turnover by the p13 protein of human T-cell leukemia virus type 1: distinct effects in primary versus transformed cells

Abstract: The present study investigated the function of p13, a mitochondrial protein of human T-cell leukemia virus type 1 (HTLV-1). Although necessary for viral propagation in vivo, the mechanism of function of p13 is incompletely understood. Drawing from studies in isolated mitochondria, we analyzed the effects of p13 on mitochondrial reactive oxygen species (ROS) in transformed and primary T cells. In transformed cells (Jurkat, HeLa), p13 did not affect ROS unless the cells were subjected to glucose deprivation, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 40 publications
1
52
0
Order By: Relevance
“…Blockade of mitochondrial complex-I in these cells reduced disease-associated hyper-expression of IL-4 (Kaminski et al, 2010(Kaminski et al, , 2013. In addition, a number of recent studies identified novel molecular players, which all affect mitochondrial ROS production and thereby T-cell activation as well as apoptosis (Kaminski et al, 2007(Kaminski et al, , 2013Silic-Benussi et al, 2010). In summary, it now clear that mitochondria have a complex and very important role in controlling T-cell function.…”
Section: When and Where Are Ros Generated?mentioning
confidence: 95%
“…Blockade of mitochondrial complex-I in these cells reduced disease-associated hyper-expression of IL-4 (Kaminski et al, 2010(Kaminski et al, , 2013. In addition, a number of recent studies identified novel molecular players, which all affect mitochondrial ROS production and thereby T-cell activation as well as apoptosis (Kaminski et al, 2007(Kaminski et al, , 2013Silic-Benussi et al, 2010). In summary, it now clear that mitochondria have a complex and very important role in controlling T-cell function.…”
Section: When and Where Are Ros Generated?mentioning
confidence: 95%
“…It accumulates in the inner membrane of the mitochondria and modulates K ϩ permeability and reactive oxygen species, thereby altering the morphology and function of mitochondria. [25][26][27] Evidence of p13 expression in HTLV-1-infected cells is indirect, because only the presence of mRNA has been demonstrated in both in vitro and ex vivo studies. [28][29][30] orf -II appears to be dispensable for viral infection and transformation of T cells in vitro; however, its requirement in HTLV-1 infection of rabbits remains uncertain because the mutation introduced into the HTLV-1 molecular clone to ablate p13 also affected the HBZ gene.…”
Section: Introductionmentioning
confidence: 99%
“…Since the interaction of TRX-ASK1 is not affected by Nox isozyme-derived ROS (41), it is unlikely that Nox5␣ participates in the ADF/ASK1 pathway. p13, a HTLV-1-encoded protein located in mitochondria, also increases ROS generation and thereby induces the death of HTLV-1-infected cells, contributing to the turnover between normal and HTLV-1-transformed cells (42). However, Nox-dependent ROS generation is not affected by the mitochondrial oxidase inhibitor rotenone and appears to be functionally different from mitochondrial ROS production (14).…”
Section: Htlv-1 Is the Causative Agent Of Atl A Cd4mentioning
confidence: 91%